DEVELOPMENT OF THE METHOD OF IMPROVING THE SELECTION OF DIELECTRICAL STRENGTH ELEMENTS OF OPTICAL CABLE DESIGN - STEPANOV, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper considers the development of method for improving the selection of central and peripheral strength elements (SE) on the example of construction of a single-winding dielectric self-supporting optical cable (DSSOC) based on the determination of the dependence of the specified tensile load provided by the SE on the the parameters of its core. The research carried out in the work made it possible to improve the process of selecting the strength elements of the DSSOC and to establish that the dependences of the tensile loads of the central (CSE) and peripheral (PSE) SE have a different character. It was found that the diameter of the central strength element is the determining parameter of the cable core when determining the values ​​of F'СSЕ and F'PSЕ. The results of the calculation of the tensile loads of the CSE and the PSE of the selected model are shown that the use of aramid threads in the PSE layer gives a contribution to the total value of the maximum permissible tensile load (MPTL) approximately an order of magnitude greater than that of the fiberglass core of the CSE. According to the developed method, an example of the selection of strength elements of the DSSOC structure with 18 aramid threads is shown, which ensured the value of the MPTL in the cable by 12.3 % more than the needed value. In addition, the study of the accelerated selection of strength elements of the DSSOC core design models is shown that with the correct selection of the CSE diameter, optimization of the cable design is possible. For this purpose, a graphic model of the implementation of the method was developed and the dependencies between the tensile loads provided by the cable strength elements and the parameters of the design model were obtained, which allows to significantly reduce the time of choosing the optimal strength elements, the structure of the core and the parameters of other structural elements to ensure the specified MPTL and reducing the total cost of the cable.
Keywords: optical cable; strength elements; fiberglass rod; aramid threads; maximum tensile load; maximum allowable elongation